Legislative regulation of commercial use of intellectual property objects in business activities - Andrii Khridochkin; Larysa Harmider; Anastasia Lomakina; Marina Ivanova (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2024)
The article analyzes current issues of the modern process of legislative regulation of the commercial use of intellectual property objects in entrepreneurial activity. Specific proposals regarding strategic directions for further improvement of the organizational and legal foundations of the process of commercial use of intellectual property objects in entrepreneurial activity are proposed, which should be focused on solving the following three blocks of current problems: problems of the legislative, institutional and infrastructural basis of the commercial use of objects intellectual property in business activities. Attention is focused on the need to systematize Ukrainian legislation on legal responsibility for infringement of rights to intellectual property objects used in business activities, adaptation of current domestic normative legal acts in the field of intellectual property to the relevant acts of the European Union, legislative regulation of the issue of disposal of objects intellectual property used in business activities, creation of a modern basis for the protection of intellectual property objects in the military-technical sphere, as well as improvement of the existing legal framework of the system of collective management of property copyright and related rights. The presence of a need to improve the institutional basis of the process of commercial use of intellectual property objects used in entrepreneurial activity in the direction of implementing the concept of a single intellectual property body created in our country, the completion of the process of commercial use of intellectual property objects used in entrepreneurial activity by specialists of high level, establishment of cooperation between public and private organizations, deepening of cooperation with international organizations in this field, establishment of cooperation with relevant public authorities of other states, proper support of the functioning of public organizations in the field of intellectual property. The priority of the task of improving the infrastructural base of the process of commercial use of intellectual property objects used in entrepreneurial activity is emphasized.